Research on Higher Education and Europeanization - Ertl, Hubert [Verfasser]; Eeva, Katri [Verfasser] (My University, 2018)
"One way of conceptualizing Europeanization in the context of higher education is to regard it as a specific form of internationalization of higher education. Internationalization usually entails discourses surrounding study abroad programs and internationally oriented curricula, both aimed at preparing students for living and working in international contexts. In this discourse, internationalization of higher education is perceived as a humanist project, aimed at transcending limitations and restrictions posed by national contexts, overcoming provincialism, and opening up larger cultural and social spaces." (excerpt ; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; I 2.2 Europa; Hochschulbildung; Europäische Integration; Europäische Union; Internationalisierung